2009
DOI: 10.1007/s12583-009-0012-3
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics of convergence and deformation in Luzon Island and adjacent sea areas: 2-D finite-element simulation

Abstract: The Luzon Island is a volcanic arc sandwiched by the eastward subducting South China Sea and the northwestward subducting Philippine Sea plate. Through experiments of plane-stress, elastic, and 2-dimensional finite-element modeling, we evaluated the relationship between plate kinematics and present-day deformation of Luzon Island and adjacent sea areas. The concept of coupling rate was applied to define the boundary velocities along the subduction zones. The distribution of velocity fields calculated in our mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…After the SCS opening the upward throughflow slowed down but the conductive heat flux increased relatively. Liu et al (2009) used the finite-element method again but for simulating the convergent of the SCS with the Philippine Island arc. They found that the movement of the Philippine Sea plate toward the azimuth 330° best explains the GPS pattern observed in the Luzon Island, and the coupling rate in the Manila trench is much smaller compared with the rates in the eastern Luzon trough and the Philippine trench.…”
Section: Dynamics Of the South China Seamentioning
confidence: 99%
“…After the SCS opening the upward throughflow slowed down but the conductive heat flux increased relatively. Liu et al (2009) used the finite-element method again but for simulating the convergent of the SCS with the Philippine Island arc. They found that the movement of the Philippine Sea plate toward the azimuth 330° best explains the GPS pattern observed in the Luzon Island, and the coupling rate in the Manila trench is much smaller compared with the rates in the eastern Luzon trough and the Philippine trench.…”
Section: Dynamics Of the South China Seamentioning
confidence: 99%